The importance of wide-field foreground removal for 21 cm cosmology: a demonstration with early MWA epoch of reionization observations - Pober, J.; Hazelton, B.; Beardsley, A.; Barry, N.; Martinot, Z.; Sullivan, I.; Morales, M.; Bell, M.; Bernardi, G.; Bhat, N.; Bowman, J.; Briggs, F.; et al. (Institute of Physics Publishing, 2016)
In this paper we present observations, simulations, and analysis demonstrating the direct connection between the location of foreground emission on the sky and its location in cosmological power spectra from interferometric redshifted 21 cm experiments. We begin with a heuristic formalism for understanding the mapping of sky coordinates into the cylindrically averaged power spectra measurements used by 21 cm experiments, with a focus on the effects of the instrument beam response and the associated sidelobes. We then demonstrate this mapping by analyzing power spectra with both simulated and observed data from the Murchison Widefield Array. We find that removing a foreground model which includes sources in both the main field-of-view and the first sidelobes reduces the contamination in high k_parallel modes by several percent relative to a model which only includes sources in the main field-of-view, with the completeness of the foreground model setting the principal limitation on the amount of power removed. While small, a percent-level amount of foreground power is in itself more than enough to prevent recovery of any EoR signal from these modes. This result demonstrates that foreground subtraction for redshifted 21 cm experiments is truly a wide-field problem, and algorithms and simulations must extend beyond the main instrument field-of-view to potentially recover the full 21 cm power spectrum.